Synthesis, characterization and corrosion inhibition evaluation of a new chalcone derivative 2-3-(3-hydroxyphenyl)-1-[4-(1H-imidazol-1-yl) phenyl] prop-2-en-1-one for mild steel corrosion in 1M HCl assessment with DFT and MD studies - Vidyashree G; K. Manjunatha; Bharath K. Devendra; Shweta G.M; Lokesha Poojary; Praveen B.M; Manohar R. Rathod; K. Sunil; Vijaylaxmi T. Talawar (Results in Surfaces and Interfaces)
The prime objective of the work focuses on the synthesis of novel chalcone derivative, the 2-3-(3-hydroxyphenyl)-1-[4-(1H-imidazol-1-yl) phenyl] prop-2-en-1-one (HIPP) and study its corrosion inhibition for mild steel in 1M HCl. Various spectroscopic techniques such as IR, 1H-NMR, 13C-NMR, and mass spectroscopy were used to confirm the formation of the synthesized chalcone. Distinct electrochemical techniques like potentiodynamic Tafel polarization and impedance spectroscopy were employed to investigate HIPP in 1M HCl as a mild steel corrosion inhibitor. The synthesized chalcone was checked in a temperature range varying from 30° C to 60° C. With increasing quantities of HIPP, it is noticed that there is an enhancement in calculated corrosion inhibition efficiency. The maximum inhibition efficiency obtained was found to be 94.3 % in the presence of 100 ppm at room temperature. Surface morphology of unhindered and inhibited HIPP was analysed using scanning electron microscopy (SEM), atomic force microscopy (AFM) and water contact angle (WCA) measurements. SEM investigation revealed that the inhibitor effectively protects the metal surface from aggressive corrosion. Atomic force microscopic images show the corroded MS surface roughness in the presence of HIPP reduced from 342.1 nm to 174.3 nm. Furthermore, the inhibitor's adsorption through electron-donor acceptor interactions was revealed by DFT calculations and MD studies.